2009
DOI: 10.1142/s0219720009003947
|View full text |Cite
|
Sign up to set email alerts
|

Can Complex Cellular Processes Be Governed by Simple Linear Rules?

Abstract: Complex living systems have shown remarkably well-orchestrated, self-organized, robust, and stable behavior under a wide range of perturbations. However, despite the recent generation of high-throughput experimental datasets, basic cellular processes such as division, differentiation, and apoptosis still remain elusive. One of the key reasons is the lack of understanding of the governing principles of complex living systems. Here, we have reviewed the success of perturbation-response approaches, where without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 66 publications
0
27
0
Order By: Relevance
“…1 is , F is a vector of the unknown non-linear function which includes diffusion and reaction terms, and X = ( X 1 , X 2 , .., X n ) is the species response profiles2829. For a fixed perturbation, the resultant changes in species profiles can be written by X = X 0 + δ X , where X 0 is the reference steady-state vector and δ X is the relative response from steady-states ( δ X t = 0 = 0).…”
Section: Resultsmentioning
confidence: 99%
“…1 is , F is a vector of the unknown non-linear function which includes diffusion and reaction terms, and X = ( X 1 , X 2 , .., X n ) is the species response profiles2829. For a fixed perturbation, the resultant changes in species profiles can be written by X = X 0 + δ X , where X 0 is the reference steady-state vector and δ X is the relative response from steady-states ( δ X t = 0 = 0).…”
Section: Resultsmentioning
confidence: 99%
“…Data from a wild-type macro phage were used to train the initial model, and data from two mutant macrophages were used to test the model's predictive capacity. Despite the widely accepted notion that the immune response is unpredictable, we showed that the intracellular signaling that induces proinflammatory cytokines follows the same simple rules that were first devised to explain nonliving systems (Selvarajoo et al 2009). …”
Section: Kumar Selvarajoomentioning
confidence: 85%
“…Mass action kinetics have also been used extensively, for example, to model receptor tyrosine kinase signaling [41], blood coagulation [39], pain networks [40] or Toll like receptor signaling [42], [43]. They have also been a key component in the success of perturbation-response approaches which have shown that simple linear rules often govern the response behavior of biological networks [44]. The ODE model was deterministic and captured only population averaged behavior.…”
Section: Resultsmentioning
confidence: 99%